UJI VALIDITAS ALAT PERCOBAAN KINEMATIKA GERAK LURUS SEBAGAI MEDIA PEMBELAJARAN IPA FISIKA SMP - Muhammad Ridho; Hendar Sudrajat; Fakhruddin Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was aimed to produce linearkinematics motions’ experimental tools and the valid uquipments’ guidebook so that can be used as the proper physics science learning media for junior high school student on particle material. Research and development was used as research method. Development stage consist of preliminary research, planning, the making and validating. In this research the experimental tools just were developed up to the validation stage. The data was obtained from the validation 3 lecturers and 2 teachers as validator. The validation stage I while validation stage II. The assessment was asses some aspects of experimental tools. The function of equipment got 3.67 of average value (very high category), element of learning was 3.60 (very high category), the ease was 3.45 (very high category), the aesthetic abd contruction was 3.60 (very high category),and safety was 3.60 (very high category). The aspects which were assessed from guidebook were the content accuracy which got 3.47 (very high category), the properness of presentation was 3.60 (very high category), language properness was 3.40 (very high category), and display properness was 3.40 (very high category). Each indicator of assessment were valid which categorize in very high category, this was relate to purpose of development. Based on that, it can be concluded they the kinematic linear motion experimental tools and the guidebook were valid based on the assessment in every indicators, so it can be the proper physics science learning media for junior high school on motion on particle material.Keywords : Linear kinematics experimental tools, junior high school physics sciencelearning media.